Agronomic trait selection and pre-germinative treatments in passion fruit hybrid - Oliveira, Cíntia Patrícia Martins [UNESP]; Faria, Glaucia Amorim [UNESP]; Ferreira, Antonio Flavio Arruda (FapUNIFESP (SciELO), 2022)
Seed biometry and dormancy overcoming methods should be considered in the passion fruit production chain, in the seedling production stage, because of the different characteristics that condition the seedlings. The objective of this work was to identify and correlate the main biometric characteristics between seeds and seedlings and to select the best pre-germinative treatments in passion fruit hybrids. Seed length, width, thickness and weight were measured, and subsequently subjected to pre-germinative treatments, in a completely randomized design, in a 5 x 2 x 3 (GA3 concentrations x scarification x hybrids) factorial scheme. In the initial development of the seedlings, the length of the aerial part, the diameter of the stem and the number of leaves were evaluated. Pearson’s correlation matrix was estimated between seed and seedling characters and, subsequently, path analysis. The Classification Sum Index was used for the means of the characters under pre-germinative treatment. The best pre-germinative treatment for BRS GA is scarification and soaking in 50 mg of GA3, for BRS SC, soaking in 100 mg of GA3, and for BRS RC, immersion in 50 mg of GA3. Seed morphometric selection is a technique that should be recommended to obtain quality seedlings
Keywords: Mulamba & mock index; Pearson’s correlation; Seedlings; Seeds